Grilling temperature effects on tenderness, juiciness, flavor and volatile aroma compounds of aged ribeye, strip loin, and top sirloin steaks. (April 2019) - Wall, Kayley R.; Kerth, Chris R.; Miller, Rhonda K.; Alvarado, Christine
Abstract: Ribeye, top loin, and top sirloin steaks were assigned a grilling temperature setting (177° C, 205° C, or 232° C) and consumer panel, Warner-Bratzler shear force, trained sensory panel, and GC/MS – olfactory analyses were performed. No differences (P > 0.05) in consumer overall, tenderness, juiciness, appearance, and flavor liking were detected among steak type or grill temperature. Grill surface temperature had no effect (P > 0.05) on trained panel tenderness scores. Of the volatiles present during an aroma event, pyrazine compounds were most influenced by grill surface temperature. The tenderness and juiciness of steaks grilled at differing temperatures were not perceived to be different by consumers; however, grilling temperature impacted the flavor of the final product by generating more pyrazine compounds. Steaks in this study likely were too tender to have a grilling effect on tenderness, but selecting different grilling temperatures can be used to vary the amount of browning of steaks and/or to modify aroma volatile compounds.